2019
DOI: 10.1002/ejic.201900560
|View full text |Cite
|
Sign up to set email alerts
|

General Solution‐Phase Synthesis of Nanoscale Transition Metal Tellurides Using Metal Nanoparticle Reagents

Abstract: Nanoscale transition metal tellurides are important materials for a variety of applications. However, solution-phase methods to synthesize nanoscale transition metal tellurides are not as well-developed as for related sulfide and selenide systems. Here, we show that pre-formed colloidal metal nanoparticles react with bis(trimethylsilyl)telluride to form their corresponding tellurides. Nanoparticles of Pd, Pt, and Ni convert to nanoscale particles of the layered transition metal dichalcogenides PdTe 2 , PtTe 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…There are few reports of interconversions of metal sulfide, selenide, and telluride NPs through anion exchange, yet such interconversions would afford a range of new phases, morphologies, and nanoheterostructures based on the well-developed syntheses of metal sulfides and selenides. This is especially important given that the direct solution synthesis of metal tellurides is often problematic due to the tendency to form tellurium oxide and the reactivity of many tellurium reagents . One route around this difficulty is the transformation of metal to metal telluride NPs under mild conditions, albeit without morphology retention .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There are few reports of interconversions of metal sulfide, selenide, and telluride NPs through anion exchange, yet such interconversions would afford a range of new phases, morphologies, and nanoheterostructures based on the well-developed syntheses of metal sulfides and selenides. This is especially important given that the direct solution synthesis of metal tellurides is often problematic due to the tendency to form tellurium oxide and the reactivity of many tellurium reagents . One route around this difficulty is the transformation of metal to metal telluride NPs under mild conditions, albeit without morphology retention .…”
mentioning
confidence: 99%
“…This is especially important given that the direct solution synthesis of metal tellurides is often problematic due to the tendency to form tellurium oxide and the reactivity of many tellurium reagents . One route around this difficulty is the transformation of metal to metal telluride NPs under mild conditions, albeit without morphology retention . In one example of the introduction of Te into a metal sulfide NP, Saruyama et al converted CdS spheres to CdS–CdTe tear drops, affording a distinct CdTe crystal system and significant morphology alteration .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, (Me 3 Si) 2 Te reacts with pre-formed colloidal metal nanoparticles of Pd, Pt and Ni under sufficiently mild conditions (180 °C, 1h) to form their corresponding ditellurides PdTe 2 , PtTe 2 , and NiTe 2 . 111 Other metal nanoparticles of Co, Ag, and Rh also form crystalline metal tellurides upon reaction with (Me 3 Si) 2 Te, indicating that this approach to synthesizing nanoscale transition metal tellurides is ). 108,112,113 The shape, single crystallinity, and orientation of the parent metal oxide NPs are completely preserved in the transformed particles.…”
Section: Miscelleneous Methdsmentioning
confidence: 97%
“…Fenton et al [62] reported metal tellurides are vital materials used for different applications such as photovoltaic, catalytic and thermoelectric purposes. Hence, he came up with a novel method of synthesising the nanoscale transition metal tellurides by the interaction of pre-formed colloidal metal nanoparticle and bis(trimethylsilyl)telluride using solution-phase synthesis.…”
Section: Synthesis Of Inorganic Compoundsmentioning
confidence: 99%